Pejabat Daerah Kota Tinggi (PDKT) / Nabilah Zakaria - Zakaria, Nabilah (Universiti Teknologi MARA, Sarawak, 2016)
Pejabat Daerah Kota Tinggi was located in Aras 2, Bangunan Sultan Iskandar, in Kota Tinggi, Johor. Administrative area includes 10 districts with population estimates 200,000 people who are subscribers to the service provided in this office. Pejabat Derah Kota Tinggi is a department responsible Kota Tinggi in regional development and at the same time introduce Kota Tinggi in the eyes of the world. The department is also a centre for change, challenge and influence in social and cultural forms. In addition, the Pejabat Daerah Kota Tinggi also serves as institutional development support in the grassroots level in every area in the district of Kota Tinggi. The higher administrator of this office and in the town called Pegawai Daerah (District Officer), which normally being changed every five to six years as being promoted by the city council. His official home can be seen nearby the field of the city called Padang Kerajaan Kota Tinggi, nearby the highest building located the administration of Kota Tinggi government which is the Bangunan Sultan Iskandar.